Political Ethics as A Way to Perfect Religious Humanism - Muhammad Danil; Melia Rosa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The ethics of a politician are a necessity to pay attention to in perfecting religious humanism in the world of politics so that it can produce policies that support a prosperous and prosperous society. However, so far what we have encountered has only been limited to campaigning in the stage of gaining the most votes. The speakers related to political ethics, religious ethics, and the relationship between religion and politics have been discussed by figures such as Al Farabi, Ibnu Taymiyah, Miroljub Jevtic, Anthony Gill and others. Therefore, research like this should continue to be carried out so that the results will have a positive impact on politics and our society in the future. Research related to ethics was carried out using library research where the sources were taken from materials that focused on highlighting ethics, politics and religion with a data processing process that went through several stages starting with data coding and ending with drawing conclusions. The results of this research determine that the ethics that must be present in a politician to perfect his religious humanism are related to justice, honesty, responsibility, and broad knowledge which are crucial to the formation of a prosperous and prosperous society which can give birth to a civilization of high value.